2020
DOI: 10.1016/j.sleh.2020.05.002
|View full text |Cite|
|
Sign up to set email alerts
|

Does context matter? A multilevel analysis of neighborhood disadvantage and children's sleep health

Abstract: Objectives: To determine how demographic, socioeconomic, and neighborhood characteristics are associated with bedtimes among US kindergarteners. Design: Parents reported bedtimes of their children as well as personal, household, and residential characteristics via interviews in the Early Childhood Longitudinal Study-Kindergarten (ECLS-K) Class of 1998-1999. The ECLS-K links individual households to US Census tracts. Setting: A random selection of 1,280 schools and surrounding communities in the US. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Lower family income-to-needs ratio and parental education were associated with later weekday and weekend sleep midpoints in children. These findings are consistent with those of previous studies linking socioeconomic disadvantage with later bedtimes in children (4,(22)(23)(24)(25)(26). Later sleep midpoint may suggest that sleep timing is misaligned with optimal functioning of the circadian system (28).…”
Section: Socioeconomic Disadvantage Is Associated With Later Sleep Ti...supporting
confidence: 93%
See 1 more Smart Citation
“…Lower family income-to-needs ratio and parental education were associated with later weekday and weekend sleep midpoints in children. These findings are consistent with those of previous studies linking socioeconomic disadvantage with later bedtimes in children (4,(22)(23)(24)(25)(26). Later sleep midpoint may suggest that sleep timing is misaligned with optimal functioning of the circadian system (28).…”
Section: Socioeconomic Disadvantage Is Associated With Later Sleep Ti...supporting
confidence: 93%
“…Later sleep timing has been related to delayed circadian functioning and sleep problems (21). Socioeconomic disadvantage has been frequently associated with later bedtimes in children (4,(22)(23)(24)(25)(26). Fewer studies have focused on sleep midpoint, which captures variability in both bedtime and wake-up time.…”
Section: Socioeconomic Disparities In Sleep Duration and Timingmentioning
confidence: 99%
“…Research in preschool children (approximately 2.5-5 years of age) has prioritized home-based interventions, or interventions targeting obesity rather than sleep as a primary outcome . Despite sleep health disparities, population samples have lacked racial, ethnic, and socioeconomic diversity . Half of the nation’s preschoolers attend early childhood programs, in which promoting sleep health is endorsed by parents and staff .…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in sleep behaviours of young children based on ethnicity, income, and mother's level of education have been noted (75). Recent research has shown that parents of Hispanic children were more accurate at estimating their child's sleep duration and wake time than parents of White children (76).…”
Section: Summary Of Main Findingsmentioning
confidence: 99%